The economics of organised crime - Fiorentini, Gianluca, 1962-; Peltzman, Sam; Centre for Economic Policy Research (Great Britain); Università di Bologna. Department of Economics (Cambridge : Cambridge University Press, 1995)
This is the first book to use economic theory in the analysis of all the different aspects of organised crime: the origins, the internal organisation, market behaviour and deterrence policies. The theory of rent-seeking is adopted to help understand the origin of criminal organisations from a state of anarchy, while modern industrial organisation theory is used to explain the design of internal rules in the organised crime sector. The market behaviour of organised crime is analysed taking into account its double nature of competitive firm and of monopolist on rule-making. Finally, the'crime and economics' approach is applied to the analysis of corruption that occurs when the organised crime sector and the government collude to exploit their monopoly on rule-making. This book provides a careful balance between theoretical and institutional or empirical contributions. Each chapter outlines the normative results of the analysis in order to design more sophisticated deterrence policies.
Introduction / Gianluca Fiorentini and Sam Peltzman -- Organised Crime, Mafia and Governments / Annelise Anderson -- Gangs as Primitive States / Stergios Skaperdas and Constantinos Syropoulos -- Internal Cohesion and Competition Among Criminal Organisations / Michele Polo -- Conspiracy Among the Many: The Mafia in Legitimate Industries / Diego Gambetta and Peter Reuter -- Rival Kleptocrats: The Mafia Versus the State / Herschel I. Grossman -- Corruption: Arm's-Length Relationships and Markets / Vito Tanzi -- Auditing With'Ghosts' / Frank A. Cowell and James P.F. Gordon -- The Reputational Penalty Firms Bear from Committing Criminal Fraud / Jonathan M. Karpoff and John R. Lott, Jr. -- Regulating the Organised Crime Sector / Marco Celentani, Massimo Marrelli and Riccardo Martina -- Oligopolistic Competition in Illegal Markets / Gianluca Fiorentini.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Organized crime -- Economic aspects; Mafia -- Economic aspects